2012
DOI: 10.1088/0004-637x/752/2/161
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy-Based Thermal Evolution of Loops. Ii. Improvements to the Model

Abstract: This paper develops the zero-dimensional (0D) hydrodynamic coronal loop model "Enthalpy-based Thermal Evolution of Loops" (EBTEL) proposed by Klimchuk et al (2008), which studies the plasma response to evolving coronal heating, especially impulsive heating events. The basis of EBTEL is the modelling of mass exchange between the corona and transition region and chromosphere in response to heating variations, with the key parameter being the ratio of transition region to coronal radiation. We develop new models … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
164
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(171 citation statements)
references
References 27 publications
7
164
0
Order By: Relevance
“…We also use another free parameter to characterize the loss term through the transition region. Instead of computing this loss term using an equilibrium solution (Cargill et al 2012a), we scale this term as being proportional to the mean coronal pressure P á ñ by a scaling constant η. Such proportionality is observed in the decay phase of solar and stellar flares as well as predicted in coronal heating models (Hawley & Fisher 1992;Qiu et al 2013, and references therein).…”
Section: D Modeling Of 12500 Loopsmentioning
confidence: 99%
“…We also use another free parameter to characterize the loss term through the transition region. Instead of computing this loss term using an equilibrium solution (Cargill et al 2012a), we scale this term as being proportional to the mean coronal pressure P á ñ by a scaling constant η. Such proportionality is observed in the decay phase of solar and stellar flares as well as predicted in coronal heating models (Hawley & Fisher 1992;Qiu et al 2013, and references therein).…”
Section: D Modeling Of 12500 Loopsmentioning
confidence: 99%
“…However, it is unclear how successfully this formalism translates into dynamic evolution. The increase in coronal density after heating arises precisely because the transition region is not in equilibrium: the downward heat flux exceeding the radiative losses, leading to an upward enthalpy flux (see Klimchuk et al 2008;Cargill et al 2012). In the decay of impulsive events, the coronal properties are governed by a downward enthalpy flux responsible for the transition region radiation: conduction plays a minimal role (Bradshaw 2008;Bradshaw & Cargill 2010a, 2010b.…”
Section: Implications For Multi-dimensional Mhd Modelsmentioning
confidence: 99%
“…Hotter loops require smaller grid cells and longer loops can be modeled with wider cells. Such resolutions are straightforward in static loop models, either by brute force or especially using thermally structured grids (e.g., Appendix A of Cargill et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The net loss includes the optically-thin radiative loss in the corona and an amount of loss through the transition region, part of which will be radiated by the chromosphere. The loss through the transition region is either directly scaled to the coronal radiative loss with a free scaling parameter (Klimchuk et al 2008), or estimated by taking into account the atmosphere stratification (Cargill et al 2012a). In this study, we have computed loop evolution with both versions of the code, and found that the difference is only about 10% in both the temperature and density values.…”
Section: Modeling Of the Two Sets Of Flare Loopsmentioning
confidence: 97%
“…We use these heating rates to compute plasma evolution in flare loops using the zerodimensional (0D) model called "enthalpy-based thermal evolution of loops" (EBTEL; Klimchuk et al 2008;Cargill et al 2012a) in this study. The EBTEL model computes evolution of the average temperature and density in a coronal loop given an impulsive energy input, which has been validated by advanced one-dimensional (1D) hydrodynamic simulations.…”
Section: Introductionmentioning
confidence: 99%